The effect of chaotic recurrence and financial events on stock market (2015)
Company´s market share price can be affected by financial events or be a consequence of the stock market chaotic trend. This effect also depends on company market capitalization. In technical analysis of the stock market, chaotic recurrence analysis can help to determine whether this impact comes from a market chaotic long-term trend or financial events. Therefore, the purpose of the study was to analyze whether the issuers´ share price reaction in the stock market is a consequence of financial events or a chaotic trend in the market. The share value of three representative companies in the Colombian stock exchange during the years 2006-2010 were analyzed. The companies were selected according to their market capitalization. The fall of the Colombian market index was taken as a breakpoint. Log transformations and a nonlinear recurrence analysis model were applied to these data. The recurrence analysis was fit to the data series before the fall of the Colombian market index and then to the entire time series. Model parameters, such as laminarity, determinism, recurrence, entropy, trapping time, delay and embedded dimensions were identified. Despite differences existed in recurrence plots, all of the quantitative recurrence analysis parameters were the same in all models, and the breaking point had no effect on them. The conclusion was that a strong chaotic recurrence exists, which shadows the effect of the market index fall.